SISTEM INFORMASI PENJUALAN RUMAH DAN PROMOSI MENGGUNAKAN BAHASA PEMROGRAMAN PHP DAN DATABASE MySQL - Kurniawan, Jefdy; Afianto, Dafit (Jurnal Informatika Medis, 2023)
Marketing of conventional housing will need money, time and considerable power while the consumers still need detailed information before making purchases home. Seeing a lot of promising things out of the utilization of technology, especially information technology. Developments in information technology have brought many changes to the sector of the business activity is run in the real world. The changes are marked by a number of efforts of the business activity sector which was originally based in the real world, then develop into the cyberspace. Given the extent of the intended market of Filano Land is quite spacious. At this time the system is applied to Filano Land has made the development of the promotion sector on the web-based but the information has given incomplete that has required by prospective customers. Seeing this, should be done improvements in terms of sales information and promotion of products on Filano land.